Pelatihan Sistem Manajemen Aplikasi SISKA Untuk Pengisian KRS Mahasiswa Berbasis WEB Di Universitas Bumigora - Fahry, Fahry; Febriana, Widia; Asroni, Ondi; Urfina, Yasyifa Dian (CV. Global Cendekia Inti, 2024)
SISKA Application Management System (Study Plan Card Filling Information System) is a web-based application designed to facilitate the process of filling out student Study Plan Cards (KRS) at Bumigora University. This application aims to improve the efficiency and effectiveness of the KRS filling process, as well as facilitate students in accessing academic information. By using web-based technology, the SISKA application allows students to access and fill out KRS online, as well as monitor the status of KRS filling in real-time. In addition, this application can also assist lecturers and academic staff in managing KRS data and monitoring student academic progress. SISKA application was developed using PHP programming language and MySQL database, and designed with an intuitive and easy-to-use user interface. Thus, SISKA application can be an effective and efficient solution to improve the quality of academic services at Bumigora University.